The rates of lumbar spinal stenosis surgery in Norwegian public hospitals: a threefold increase from 1999 to 2013 - Grøvle, Lars; Fjeld, Olaf Randall; Haugen, Anne Julsrud; Helgeland, Jon; Småstuen, Milada Cvancarova; Solberg, Tore; Zwart, John-Anker; Grotle, Margreth (Spine, 2018)
Accepted manuscript version of the following article: Grøvle, L., Fjeld, O.R., Haugen, A.J., Helgeland, J., Småstuen, M.C., Solberg, T., . Grotle, M. (2018). The rates of lumbar spinal stenosis surgery in Norwegian public hospitals: a threefold increase from 1999 to 2013. Spine . Published version available at https://doi.org/10.1097/BRS.0000000000002858 . Study Design : Retrospective administrative database study. Objective : To assess temporal and regional trends, and length of hospital stay, in lumbar spinal stenosis (LSS) surgery in Norwegian public hospitals from 1999 to 2013. Summary of Background Data : Studies from several countries have reported increasing rates of LSS surgery over the last decades. No such data have been presented from Norway. Methods : A database consisting of discharges from all Norwegian public hospitals was established. Inclusion criteria were discharges including a surgical procedure of lumbar spinal decompression and/or fusion in combination with an ICD-10 diagnosis of Spinal Stenosis (M48.0) or Other Spondylosis with Radiculopathy (M47.2), and a patient age of 18 years or older. Discharges with diagnoses indicating deformity, i.e. spondylolisthesis or scoliosis were not included. Results : During the 15-year period, 19 543 discharges were identified. The annual rate of decompressions increased from 10.7 to 36.2 and fusions increased from 2.5 to 4.4 per 100 000 people of the general Norwegian population. The proportion of fusion surgery decreased from 19.3% to 10.9%. Among individuals older than 65 years, the annual rate of surgery per 10000, including both decompressions and fusions, more than quadrupled from 40.2 to 170.3. The regional variation was modest, differing with a factor of 1.4 between the region with the highest and the lowest surgical rates. The mean length of hospital stay decreased from 11.0 (SD 8.0) days in 1999 to 5.0 (4.6) days in 2013, but patients who received fusion surgery stayed on average 3.6 days longer than those who received decompression only. ...